Comparative Transcriptomics Unveil the Crucial Genes Involved in Coumarin Biosynthesis in Peucedanum praeruptorum Dunn - Song, Cheng; Li, Xiaoli; Jia, Bin; Liu, Li; Wei, Peipei; Manzoor, Muhammad Aamir; Wang, Fang; Li, Biqi Yao; Wang, Guanglin; Chen, Cunwu; Han, Bangxing (Frontiers in Plant Science, 2022)
Peucedanum praeruptorum Dunn is a commonly used traditional Chinese medicine that is abundant in furano- and dihydropyrano coumarins. When P. praeruptorum reaches the bolting stage, the roots gradually lignified, and the content of coumarins declines rapidly. Non-bolting has always been a decisive factor for harvesting the P. praeruptorum materials. To evaluate the amount of coumarin components in unbolted and bolted P. praeruptorum, the variations of praeruptorin A, praeruptorin B, praeruptorin E, peucedanocoumarin I, and peucedanocoumarin II were determined. Additionally, 336,505 transcripts were obtained from the comparative transcriptome data. Among them, a total of 1573 differentially expressed genes were screened out. To identify the critical genes involved in coumarin biosynthesis, comparative transcriptomics coupled with co-expression associated analysis was conducted. Finally, coumarin biosynthesis-related eighteen candidate genes were selected for the validation of qPCR. Additionally, a phylogenetic tree and the expression profile of ATP-binding cassette (ABC) transporters were constructed. To clarify the main genes in the regulation of coumarin biosynthesis, the interaction network of the co-expression genes from thirteen modules was constructed. Current results exhibited the significant increment of praeruptorin A, praeruptorin B and praeruptorin E in the bolted P. praeruptorum. Although, peucedanocoumarin I and peucedanocoumarin II were slightly increased. Besides the content of coumarins, the essential genes involved in the coumarin biosynthesis also exhibited an overall downward trend after bolting. Three peroxidases (PRXs) involved in the production of lignin monomers had been demonstrated to be downregulated. PAL, C4H, HCT, COMT, CCoAOMT, and some ABC transporters were dramatically downregulated at the bolting stage. These results indicated that the downregulation of coumarin biosynthetic genes in the bolted P. praeruptorum ultimately reduced the formation of coumarins. However, the mechanism through which bolting indirectly affects the formation of coumarin still needs extra functional verification.